Analyzing the Local Budget Revenues in the Implementation of the Reform of Budget Decentralization - Sokyrko Olena S. (Bìznes Inform, 2019)
The article is aimed at studying the filling of local budgets in terms of the budget decentralization, as well as searching for problems and developing recommendations to solve them. The local budgets are an instrument of financial-economic regulation of the development of regions and the State as a whole. Both the efficient formation and administration of local budgets should be based on a combination of financial-economic relationships in the area of revenue generation, implementation of budget expenditures, the inter-budgetary relations and the development together with implementation of the balanced socio-economic policies directed towards ensuring the socio-economic growth of regions. The reform of budget decentralization has provided local governments with broader rights and new sources of financial resources, which has collectively increased the financial viability and autonomy of the regions. The article indicates a number of problems that nevertheless hinder the successful development of territorial communities. First of all, there are: misuse of funds; corruption at the local level; low levels of financial literacy for local government workers; lack of investment attractiveness of regions; uneven development of the territories, etc. In order to address these problems, it would be useful to coordinate the public policy of regional development in view of the outlined problems; to monitor the competence of local governments; to help in eliminating the unhealthy political competition in the local authorities; to form expenditures from the local budget on the basis of a program-targeted method; to improve the regional infrastructure.